Science and the media : alternative routes in scientific communication - Bucchi, Massimiano, 1970- (Routledge studies in science, technology, and society, 1998)
In the days of global warming and BSE, science is increasingly a public issue. This book provides a theoretical framework which allows us to understand why and how scientists address the general public. The author develops the argument that turning to the public is not simply a response to inaccurate reporting by journalists or to public curiosity, nor a wish to gain recognition and additional funding. Rather, it is a tactic to which the scientific community are pushed by certain "internal" crisis situations. Bucchi examines three cases of scientists turning to the public: the cold fusion case.